If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + -1c) + -1 = 2(3 + -5c) (1 * 4 + -1c * 4) + -1 = 2(3 + -5c) (4 + -4c) + -1 = 2(3 + -5c) Reorder the terms: 4 + -1 + -4c = 2(3 + -5c) Combine like terms: 4 + -1 = 3 3 + -4c = 2(3 + -5c) 3 + -4c = (3 * 2 + -5c * 2) 3 + -4c = (6 + -10c) Solving 3 + -4c = 6 + -10c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '10c' to each side of the equation. 3 + -4c + 10c = 6 + -10c + 10c Combine like terms: -4c + 10c = 6c 3 + 6c = 6 + -10c + 10c Combine like terms: -10c + 10c = 0 3 + 6c = 6 + 0 3 + 6c = 6 Add '-3' to each side of the equation. 3 + -3 + 6c = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 6c = 6 + -3 6c = 6 + -3 Combine like terms: 6 + -3 = 3 6c = 3 Divide each side by '6'. c = 0.5 Simplifying c = 0.5
| -7x=11x-16 | | -4(5-2a)+3(a-4)=6(2-a)-5a | | 0.8888x=-64 | | 0.1=10n | | 0.5(2y-1)-(0.5-0.2y)+1=0 | | 6+(2-4x)+5=3(1-3x) | | 3x-5(2-x)=54 | | -15+z=11 | | 20+x-4=-1+16 | | 20+x-4=2x-8 | | x(.08)+X=240 | | xx=x | | 8x-5x-3x-2=13 | | 8=2x-4+6 | | 2ax^2-ax^2= | | (2)x-x-3=-2 | | K+28=26 | | 33=9-2h | | 2c+3d+4c-d= | | 5.80+0.75a=10.30 | | -2x^3y*-x^3y= | | -2x^3y*x^3y= | | 1.8t=-54 | | m+6=-35 | | 7.7=x-2.5 | | 2-3x=3-11 | | S=3a+6b | | 7b*b= | | 13x+19y=173 | | 5(3x-2)-14x=4 | | 52+10=n | | -8+7y+5=y-39 |